2008
DOI: 10.1123/jsm.22.3.322
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Assessment of Spectator-Based Brand Equity

Abstract: Few studies in the branding literature have approached brand equity from the sport perspective, and even fewer studies focus on the construct from the consumer viewpoint. The purpose of the current research was to empirically test the spectator-based brand equity (SBBE) model. Using a sample from professional basketball consumers, the results of the study show that the 49-item, 13-construct model has a reasonable fit to the data. The study extends the understanding of sport brand equity from the consumer persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(110 citation statements)
references
References 26 publications
6
101
1
2
Order By: Relevance
“…In order for individuals to hold favorable thoughts regarding a brand, they must first be aware of the brand. Therefore, numerous authors have hypothesized that brand awareness influences brand associations (Aaker, 1996;Gladden, et al, 2001;Keller, 1993;Ross, 2006;Ross et al, 2008). Consumers who have a high level of familiarity with a brand have more depth and breadth of thoughts about the brand and are more likely to have a positive disposition toward the brand (Campbell & Keller, 2003).…”
Section: Figure 3 Hypothesized Causal Modelmentioning
confidence: 99%
“…In order for individuals to hold favorable thoughts regarding a brand, they must first be aware of the brand. Therefore, numerous authors have hypothesized that brand awareness influences brand associations (Aaker, 1996;Gladden, et al, 2001;Keller, 1993;Ross, 2006;Ross et al, 2008). Consumers who have a high level of familiarity with a brand have more depth and breadth of thoughts about the brand and are more likely to have a positive disposition toward the brand (Campbell & Keller, 2003).…”
Section: Figure 3 Hypothesized Causal Modelmentioning
confidence: 99%
“…Building on these insights, Kunkel, Doyle, Funk, Du, and McDonald (2016) (Doyle, Kunkel, & Funk, 2013b;Funk & James, 2006), merchandise purchase (Kwon & Kwak, 2014), and media consumption (Doyle et al, 2013b). Researchers, however, have typically focused on the influence of brand associations on loyalty (Bauer et al, 2008;Doyle et al, 2013a;Funk & James, 2006;Gladden & Funk, 2001;Ross et al, 2008). Biscaia et al (2013) did test the influence of brand associations on behavioral intentions; however, they operationalized intentions with 7-point Likert scale items and called for future research to test the reliability of the findings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the case of the management factor, some researchers have arrived at the conclusion that good and strong managers with desirable capability and ability have a significant and positive effect on brand equity of professional football clubs (12,15). Additionally, in line with the success factor of the team, it has been observed that team success is an effective factor for brand equity of basketball and football clubs (12,16).…”
Section: Figure 1 Structural Model Values Of T and Factor Weight Ofmentioning
confidence: 99%
“…Plus, research results show that head coach has effect on brand equity of football teams in the US Universal Football League (12,17,18). In line with the stadium factor, dissertations have introduced the role of good, modern, and equipped stadia in brand equity of professional football and basketball clubs (12,15,16). Also, in line with the factor of sponsors, they have found that sponsoring is one of the effective factors on brand equity of professional football clubs (19,20).…”
Section: Figure 1 Structural Model Values Of T and Factor Weight Ofmentioning
confidence: 99%
See 1 more Smart Citation